A new calculation method for tooth fillet foundation stiffness of cracked spur gears. (March 2021) - Yang, Lantao; Wang, Liming; Shao, Yimin; Mechefske, Chris K.; Chen, Qiuyuan
Highlights: A new calculation method for calculating the tooth fillet foundation stiffness of cracked spur gears is proposed. The proposed method can meet the calculation of the fillet foundation stiffness for both the tooth and rim cracked gears. The new method can be employed to calculate the mesh stiffness of the cracked gear more accurately. Abstract: General calculation methods for tooth fillet foundation stiffness will generate significant errors in the rim crack case. In order to solve this problem, a new calculation method is proposed in this paper, which is capable of taking both tooth and rim cracks into account. In the proposed method, the root position of the cracked gear tooth is redefined using the connecting line between the crack vertex and the transition curve endpoint. The tooth fillet foundation stiffness of the cracked gear with different crack parameters can then be calculated. The calculation results using this new method are validated by finite element method (FEM) results. The calculation results of cracked gears based on the proposed method are in good agreement with FEM. The proposed method can meet the calculation of the fillet foundation stiffness for both tooth and rim cracked gears. The new method can be employed to calculate the mesh stiffness of the cracked gear more accurately and further to serve the fault diagnosis process of the spur gear system.